Avoiding the Learning Curve for Transcatheter Aortic Valve Replacement - Sergey Gurevich; Ranjit John; Rosemary F. Kelly; Ganesh Raveendran; Gregory Helmer; Demetris Yannopoulos; Timinder Biring; Brett Oestreich; Santiago Garcia (Cardiology Research and Practice)
Objectives. To evaluate whether collaboration between existing and new transcatheter aortic valve replacement (TAVR) programs could help reduce the number of cases needed to achieve optimal efficiency. Background. There is a well-documented learning curve for achieving procedural efficiency and safety in TAVR procedures. Methods. A multidisciplinary collaboration was established between the Minneapolis VA Medical Center (new program) and the University of Minnesota (established program since 2012, n=219) 1 year prior to launching the new program. Results. 269 patients treated with TAVR (50 treated in the first year at the new program). Mean age was 76 (±18) years and STS score was 6.8 (±6). Access included transfemoral (n=35, 70%), transapical (n=8, 16%), transaortic (n=2, 4%), and subclavian (n=5, 10%) types. Procedural efficiency (procedural time 158±59 versus 148±62, p=0.27), device success (96% versus 87%, p=0.08), length of stay (5±3 versus 6±7 days, p=0.10), and safety (in hospital mortality 4% versus 6%, p=0.75) were similar between programs. We found no difference in outcome measures between the first and last 25 patients treated during the first year of the new program. Conclusions. Establishing a partnership with an established program can help mitigate the learning curve associated with these complex procedures.